Proposal of a method to assess and report the extent of residual neurovascular tissue present in radical prostatectomy specimens. (19th April 2013) - Schatloff, Oscar; Kameh, Darian; Giedelman, Camilo; Samavedi, Srinivas; Abdul‐Muhsin, Haidar; Coelho, Rafael F.; Kang, Sung Gu; Palmer, Kenneth J.; Patel, Vipul R.
Abstract : Objective: To propose a method to assess and report the amount of neurovascular tissue present in radical prostatectomy (RP) specimens. Patients and Methods: The data of 133 consecutive patients who underwent robot‐assisted RP by a single surgeon (V.R.P.) were prospectively collected. Degree of nerve sparing (NS) was graded intraoperatively by the surgeon independently at either side as complete, partial or none. A pathologist who was 'blinded' to the surgeon's classification measured the following parameters at the posterolateral aspect of the apex, base and mid prostate at either side of the RP specimen: length, width and area of neural tissue, number of nerves per high‐power field and number of total slides containing neural tissue. Measurements were correlated to the surgeon's intraoperative perception. Results: All measurements correlated significantly with surgeon's intent of NS at all locations ( P = 0.001). Among them, the cross‐sectional area had the highest correlation coefficient (–0.550 at apex, –0.604 at mid prostate and –0.606 at the base). Conclusions: The cross‐sectional area of nerve tissue showed the highest correlation with surgeon's intent of NS at all locations. Having a standardised method of assessing and reporting residual nerve tissue allows the surgeon to objectively evaluate the quality of nerve preservation and to compare the progress of his NS technique over time.